2020
DOI: 10.2169/internalmedicine.4445-20
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Prophylactic Management of HBV Reactivation by an Information Technology Encoding System: Results of a 6-year Prospective Cohort Study

Abstract: Objective We started an information technology (IT) system that encodes the medical treatment status of hepatitis B virrus (HBV) with a 9-digit number, automatically checks for inappropriate situations occurring due to immunosuppression and chemotherapy that do not comply with the flowchart of the hepatitis B countermeasure guideline, and promotes correct HBV medical treatment in our hospital. We conducted a prospective study of HBV reactivation using this system. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…There were 6 studies including 3866 patients receiving only corticosteroids (Table S1a). 20,[67][68][69][70][71] Two studies included 1728 HBsAg+ patients. In one study, 68 8/72 (11%) patients without NA prophylaxis developed HBVr and all 8 patients were reported to have HBVr-associated hepatitis as well, but none developed liver decompensation or died.…”
Section: Corticosteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 6 studies including 3866 patients receiving only corticosteroids (Table S1a). 20,[67][68][69][70][71] Two studies included 1728 HBsAg+ patients. In one study, 68 8/72 (11%) patients without NA prophylaxis developed HBVr and all 8 patients were reported to have HBVr-associated hepatitis as well, but none developed liver decompensation or died.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…In the second study, 71 which only assessed mortality, 36/1447 (2.5%) patients without but 0/209 with NA prophylaxis were reported to have died due to HBVr (Table S2a1). In four studies including 2138 HBsAg-/anti-HBc+ patients all without NA prophylaxis 20,67,69,70 (Table S1a), the pooled HBVr rate was 3% (95%CI:1-6%; heterogeneity, p<0.01), and no patient died. In three of the latter studies providing such data, 20,67,69 only 1/338 (0.3%) patients experienced HBVr-associated hepatitis (pooled rate: 0%, 95%CI:0-2%; heterogeneity, p=1.00) and no patient developed decompensation (Table S2a2).…”
Section: Corticosteroidsmentioning
confidence: 99%
“…The authors reported that the cumulative incidence of HBV-R at 9 months was significantly higher in the corticosteroid treatment group (38 vs. 73%, P = 0.03) (63). In a recent 6-year prospective cohort study, HBV-R was reported to occur a median of 10 months (range, 4-32) after steroid administration (53).…”
Section: Corticosteroidsmentioning
confidence: 99%
“…The HBV-R rate in NHL patients has been reported to vary between 18.2 and 80%. HBV-R occurs from after a few weeks to up to 55 months after rituximab administration, indicating that rituximab represents a very high-risk factor for HBV-R (48,(53)(54)(55)(56)(57). Between 1997 and 2009, the US Food and Drug Administration (FDA) MedWatch Database reported 118 cases of HBV-R.…”
Section: Anti-cd20 Antibodies-rituximab and Ofatumumabmentioning
confidence: 99%
See 1 more Smart Citation